Opportunistic Screening Amongst 30 Years and Above with Glucometer to Detect High Risk Individuals for Developing Type II Diabetes Mellitus - Domple, Vijay K; Hadaye, Rujuta S; Wadde, Satish K (National Journal of Community Medicine, 2016)
Introduction: Prevalence of Type II Diabetes Mellitus (T2DM) is increasing globally and has reached epidemic proportions in many countries. Objective of this study was to detect high risk individuals for developing T2DM amongst the adults (30 years and above) with glucometer. Material and methods: This cross sectional study was carried out at Urban Health Training Center, Shivajinagar, Nanded between January 2016 to July 2016 amongst 506 individuals aged ≥30 years of age. The participants were interviewed by using predesigned questionnaire after obtaining verbal informed consent. The participants were asked to test random blood sugar (RBS) level by Freestyle Abbott Optium H Glucometer. The data were analyzed by Epi InfoTM 7 Version. Results: Of the 506 study subjects, 332(65%) participants had RBS > 110 mg/dl having greater risk for developing type 2 diabetes mellitus and 174 (35%) participants had RBS within normal range i.e. <110 mg/dl. In high risk group, 280 (55.34%) had RBS >110 mg/dl - ≤199 mg/dl and 52 (10.28%) had RBS ≥200 mg/dl. Conclusion: Conclusion: This present study has observed about 1/3rd participants to be at risk for development of T2DM.